SCIENTIFIC PRODUCTION ON THE NATIONAL HARM REDUCTION POLICY: A SCIENTOMETRIC STUDY - da Silva Alves, Renato; Silva Souza, Christiane; Mello Lazarini, Flaviane; Scremin, Marlete; de Pinho, Sirlaine; de Pinho Amaral, Bruno; Dayane Martins Souza, Dávila; Cardoso dos Santos, Rafael; Veloso César, Roberta; Mayra dos Santos, Flávia; Lucciane Alves Maria, Emmilly; Lilian Pereira de Oliveira, Émile; et al. (Health and Society, 2024)
Objective: to verify the level of knowledge and systematization of scientific production linked to the National Harm Reduction Policy after its implementation. Methods: scientometric study using the secondary databases United States National Library of Medicine (PubMed) and also in the Scientific Electronic Library Online, using as eligibility criteria the published articles included in the time cut of the last 13 years, available in full and in english, Spanish and Portuguese languages, articles with central theme related to the epidemiology of diseases were excluded, case studies, research in the areas of basic sciences, among others that did not fit the policy themes, an instrument was elaborated for data extraction, the selection of articles was carried out independently by the researchers, divergences were resolved with the use of the instrument elaborated, the identified articles were selected and classified through the analysis of titles and abstract, tabulated and organized in microsoft excel 2016 spreadsheets. Results: there was a predominance of publications between 2012 and 2016 with the central theme related to harm reduction, the state of Rio de Janeiro and other countries presented the highest number of publications, with no qualis classification level and with evidence level five. Conclusion: The scientific production related to harm reduction was expressed insipid, considering that the theme is of importance for public health.